PENGARUH PROFITABILITAS, FINANCIAL LEVERAGE,DAN DIVIDEND PAYOUT RATIO TERHADAPPERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTARDI BEI TAHUN 2015 - Ratih Javariani Utari; Emilia Gustini; Lukita Tripermata (Universitas Indo Global Mandiri)
Earnings management is the selection of accounting policies by management that are useful for achieving certain goals. One form of earning management is income smoothing. The income smoothing can make the information in the financial statements so unreliable that the interested parties become incapable of making the right business decisions.This study aims to analyze the effect of profitability, financial leverage, and dividend payout ratio to income smoothing either partially or simultaneously. The research was conducted at a manufacturing company listed on Indonesia Stock Exchange in 2015. The purposive sampling technique was used to obtain 26 manufacturing companies as sample members.This research uses quantitative data analysis method using SPSS version 16.00 as the processing tool. In this study where the independent variable is the income smoothing where the variable dichotomy scale, so the analysis used is Linear Regression Logistics. The dichotomy scale referred to in this research are doing income smoothing (2) and not doing income smoothing (1).Based on the results of research, Profitability, Financial Leverage, and Dividend Payout Ratio does not affect Partial Revenue Partially. However, if the effects are seen simultaneously, Profitability, Financial Leverage, and Dividend Payout Ratio affect Partial Revenue Partially.Keywords: Earning Management, Income Smoothing, Partial, Simultaneous Practice